Combination of transcriptomic, biochemical, and physiological analyses reveals sugar metabolism in Camellia drupifera fruit at different developmental stages - Liu, Zhen; Shen, Chunhui; Chen, Ruifan; Fu, Zhiqiang; Deng, Xiaomei; Xi, Ruchun (Frontiers in Plant Science, 2024)
Camellia drupifera, a species of woody oil crop of significant economic value in southern China, produces fruit seed oil. Sugar metabolism enzyme regulation is particularly important for sugar accumulation and oil synthesis in various organs, especially in the fruits. Nevertheless, the mechanisms of sugar metabolism in C. drupifera remain unclear. This study investigates the dynamic changes during four developmental stages of C. drupifera fruits, from rapid fruit enlargement to oil conversion. Photosynthetic products are rapidly transported from leaves to the fruit organs soon after synthesis; however, the transport efficiency markedly decreases after 48 hours. Through the analysis of sugar content, enzyme activity, and transcriptomic data, it was found that September is a critical period for oil conversion. During this period, the highest levels of sucrose content and SuSy-II enzyme activity are observed in the kernels. A comprehensive examination revealed that the high expression of ten genes related to sugar metabolism enzymes and sugar transport proteins in C. drupifera fruits is positively correlated with sucrose content. Notably, the expression of c158337. Graph_c0 (SPS), c166323.graph_c0 (SuSy), c159295.graph_c0 (SUC2-like), and c156402.graph_c0 (SUC2-like) is significantly elevated during the oil conversion phase. These findings provide a crucial theoretical foundation for further elucidating the molecular mechanisms of sugar metabolism in the fruits of C. drupifera, thereby offering insights that could enhance its economic yield.